Geomorphological response of sandy beach to tropical cyclones with different characteristics - Yu, Yue; Wang, Yongzhi; Qiao, Lulu; Wang, Nan; Li, Guangxue; Tian, Ziwen; Zhong, Yi (Frontiers in Marine Science, 2022)
Tropical cyclones (TCs) play important roles in the evolution of beaches. The response of beaches to a single tropical cyclone (TC) has been well reported, however, few studies have compared the responses of the same beach to TCs with different characteristics. Taking Haiyang Beach in the northern China Seas as a case study, the beach profiles before and after two TCs, Lekima and Bavi, which passed through the west and east sides of the study area, were investigated. The beach exhibited erosion at the upper foreshore and minor deposition near the mean high water level (MHW) after Lekima with subaqueous sandbars formed in the nearshore zone, whereas all the beach profiles showed little changes after Bavi. A high-resolution FVCOM model was established and eleven sensitive experiments were conducted to simulate hydrodynamic changes induced by TCs with different tracks, intensity and duration. Then the Xbeach model was used to display the beach evolution due to different TCs conditions. It is found that the significant storm surge and strong seaward bottom current induced by landward wind of the TCs passed through the west side of the study area should responsible for the beach profile changes. Negligible storm surge rise and landward bottom current related to the seaward wind of eastern path TCs can only result in little change of the beach. Swell contributes most to the wave height while has less effect on the beach changes. In this study, we conclude that the effects of TCs on beaches are primarily dependent on relative position of a beach and TCs’ tracks.